2016
DOI: 10.1177/0263617415619521
|View full text |Cite
|
Sign up to set email alerts
|

The Eighth Industrial Fluids Properties Simulation Challenge

Abstract: The goal of the eighth industrial fluid properties simulation challenge was to test the ability of molecular simulation methods to predict the adsorption of organic adsorbates in activated carbon materials. In particular, the eighth challenge focused on the adsorption of perfluorohexane in the activated carbon BAM-109. Entrants were challenged to predict the adsorption in the carbon at 273 K and relative pressures of 0.1, 0.3, and 0.6. The predictions were judged by comparison to a benchmark set of experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Competitions of this type would be similar to the Industrial Fluid Properties Simulation Challenge (IFPSC) 230 (nine editions to date), in which challenge entrants are computationally predict some thermophysical property based on limited experimental measurements on which to tune their simulations or other predictive method. For example, the 2012 and 2014 IFPSC competitions [231][232][233][234] involved prediction of adsorption isotherms for perfluorohexane adsorption on zeolite and activated carbon adsorbents, respectively, with only simple isotherms (Nitrogen and/or Argon), poresize distribution, and other structural characteristics as training data. Lastly, force field development and competitions based on open data resources like those from NIST may also adopt workflow practices similar to "continuous integration" (CI) that is widely used in software engineering.…”
Section: Nist Resources For Adsorption Measurementsmentioning
confidence: 99%
“…Competitions of this type would be similar to the Industrial Fluid Properties Simulation Challenge (IFPSC) 230 (nine editions to date), in which challenge entrants are computationally predict some thermophysical property based on limited experimental measurements on which to tune their simulations or other predictive method. For example, the 2012 and 2014 IFPSC competitions [231][232][233][234] involved prediction of adsorption isotherms for perfluorohexane adsorption on zeolite and activated carbon adsorbents, respectively, with only simple isotherms (Nitrogen and/or Argon), poresize distribution, and other structural characteristics as training data. Lastly, force field development and competitions based on open data resources like those from NIST may also adopt workflow practices similar to "continuous integration" (CI) that is widely used in software engineering.…”
Section: Nist Resources For Adsorption Measurementsmentioning
confidence: 99%
“…Competitions of this type would be similar to the Industrial Fluid Properties Simulation Challenge (IFPSC) 304 (nine editions to date), in which challenge entrants computationally predict some thermophysical property based on limited experimental measurements on which to tune their simulations or other predictive method. For example, the 2012 and 2014 IF-PSC competitions [305][306][307][308] involved prediction of adsorption isotherms for perfluorohexane adsorption on zeolite and activated carbon adsorbents, respectively, with only simple isotherms (Nitrogen and/or Argon), pore-size distribution, and other structural characteristics as training data. Lastly, force field development and competitions based on open data resources like those from NIST may also adopt workflow practices similar to "continuous integration" (CI) that is widely used in software engineering.…”
Section: Nist Resources For Adsorption Measurementsmentioning
confidence: 99%
“…In particular, force field simulations, such as molecular dynamics (MD) or Monte Carlo (MC), have been applied successfully to calculate thermodynamic and transport properties for many molecular systems. For example, a series of biannual competitions by the Industrial Fluid Properties Simulation Collective (IFPSC) have demonstrated that computational approaches can be used to predict thermodynamic and transport properties in close agreement with experimental measurements. However, computational methods that enable the accurate measurement of properties for one set of molecules, including simulation protocols and the underlying force field, are not guaranteed to be successful for a different set of molecules.…”
Section: Introductionmentioning
confidence: 99%